(untitled) (Journal of Management and Social Sciences, 2019)
This paper investigated the impact of taxation on government capital expenditure in Nigeria. Secondary data were used and were obtained from Central Bank of Nigerian (CBN) Statistical Bulletin and Federal Inland Revenue Service Website for Period 1994 to 2016. Descriptive statistics was used to describe the variables under investigation, Augmented Dickey Fuller (ADF) Unit Root Test and Johansen Co-integration tests were used to establish the stationarity and long run association among the variables while Error Correction Model (ECM) was used to establish the exact impact of taxation on capital expenditure in Nigeria. The study showed that Company Income Tax (CIT), Petroleum Profit Tax (PPT), Personal Income Tax (PIT) and Education Tax (EDT) have significant financing power on government capital expenditure. Contrarily, Value Added Tax (VAT) and Capital Gain Tax (CGT) are not significant variables affecting government Capital expenditure in Nigeria. However, co-integration result indicated that there was a long-run relationship between tax revenue and government capital expenditure. This paper, therefore, concluded that taxation revenue has significant effect on government capital expenditure in Nigeria and the Nigerian government should improve its’ efforts in ensuring that all taxes are collected to prevent revenue leakage, in order to ensure provision of adequate infrastructural facilities which translate to economic growth with a view to sustaining the welfare of it citizens.